2011
DOI: 10.1038/pj.2011.12
|View full text |Cite
|
Sign up to set email alerts
|

The toughening effect of a small amount of poly(ɛ-caprolactone) on the mechanical properties of the poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)/PCL blend

Abstract: To improve the mechanical properties of bacterial poly(3-hydroxybutyrate) [P(3HB)] and poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) [P(3HB-co-3HH)], the materials were blended with poly(e-caprolactone) (PCL). The P(3HB-co-7 mol% 3HH) cast film and the P(3HB-co-11 mol% 3HH) melt-pressed film show brittleness after aging, although unaged samples show ductile behavior. However, the addition of a small amount of PCL was found to greatly improve the toughness of the P(3HB-co-7 mol% 3HH) cast film and the P(3HB-co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…Katsumata et al27 similarly reported enhanced toughness in solvent cast PHBHHx/PCL blends with less than 20 wt % of PCL. Additionally, they suggested that addition of more than 20 wt % of PCL leads to a reduction in ductility due to the localization of stress around voids, which increase in size as more PCL is present.…”
Section: Discussionmentioning
confidence: 96%
“…Katsumata et al27 similarly reported enhanced toughness in solvent cast PHBHHx/PCL blends with less than 20 wt % of PCL. Additionally, they suggested that addition of more than 20 wt % of PCL leads to a reduction in ductility due to the localization of stress around voids, which increase in size as more PCL is present.…”
Section: Discussionmentioning
confidence: 96%
“…Biodegradable polymers have been widely used for the production of bags, sacks, and food packaging because these polymers, prepared from renewable resources, can undergo biodegradation upon disposal. 6 Recently, a number of studies on the fabrication and characterization of inorganic particle-filled PCL composites have been made. Since the 1990s, PCL blend systems have been studied extensively; these have included poly(vinyl chloride)/PCL, 2 styrene acrylonitrile/PCL, 3 poly(butylene terephthalate)/PCL, 4 and polystyrene/PCL 5 binary blend systems, and poly(epsiloncaprolactone)/poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)/PCL blend systems.…”
Section: Introductionmentioning
confidence: 99%
“…5 it is clearly detectable the generalized lack of interactions between the two polymers. With the aim of analyzing the surface morphology, a selective extraction process was done with acetone for a period of 24 h to selectively dissolve PCL [24]. In Fig.…”
Section: Tablementioning
confidence: 99%
“…Cryofractured samples of each blend were subjected to a selective extraction of PCL with acetone. Firstly, all samples were dried in an air circulation air oven at 40 ºC for 24 h and subsequently immersed in acetone for additional 24 h at room temperature to selectively remove the PCL portion which allows a better distinguish of the phase distribution in the blend [24]. Prior to sample observation of the samples before and after selective extraction, surfaces were covered with a thin layer of platinum in vacuum conditions with a sputter coater.…”
Section: Field Emission Scanning Electron Microscopy (Fesem)mentioning
confidence: 99%